Distúrbios respiratórios do sono em pacientes pediátricos portadores de fibrose cística - Lumertz, Magali Santos (2017)
Cystic fibrosis (CF) is a genetic disease which compromises the function of various organs. Respiratory system involvement is the main cause of morbidity and mortality in these patients. As in many chronic respiratory conditions, impairment of ventilation manifests initially during sleep. Sleep disordered breathing can lead to poorer control of the disease, by increasing local inflammation and respiratory exacerbations, reducing pulmonary function and impairing gas exchange, contributing to worse quality of life. Although relevant, there are limitations and contradictory findings about presence of sleep disordered breathing in pediatric CF population, due to small number of studies involving them and limited report of capnographic evaluation. Thus, the objectives of the study were to describe frequency of respiratory sleep disorders in pediatric patients with CF and to verify association between polysomnography findings (PSG) and other variables routinely assessed in waking period. From ninety one patients of multidisciplinary CF center at Hospital São Lucas Hospital (PUCRS), 54 individuals could be included in upper airway (UA) and sleep project. Of these, there was information regarding UA in 48 charts and about sleep (from PSG results recordings) in 16. All patients with PSG were included in the present study. Mean age was 11±5.6 years old, body mass index (in Z score) was 0,13±0,61 and expiratory volume in the first second (FEV1) mean was 87.95±26.21% of predicted. We found that FEV1 was correlated with mean sleep oxyhemoglobin saturation (r = 0.602, p 0.023) and with peak end-tidal carbon dioxide (EtCO2) in sleep (r = -0.645, p 0.024). In addition, presence of chronic airway colonization by Pseudomonas aeruginosa (PA) was associated with the mean EtCO2 in non-REM sleep (33±2.77 mmHg in those without colonization versus 37±1.41 mmHg in patients with chronically PA; p 0.024). Furthermore, apnea and hypopnea index per hour of sleep correlated with nadir of SaO2 (r= -0.593, p 0.015). Although our main limitation has been small sample size, we know PSG is a difficult access and execution examination, especially for pediatric population, so that previous studies involving children generally include samples between 10 to 40 CF subjects (most without sleep capnography). Finally, findings of this study corroborate previous reports suggesting sleep could serve as an early marker for respiratory disease progression in CF, although further studies are needed to assess these variables and mainly to analyze sleep carbon dioxide exchange. Thus, we conclude some groups that may benefit more from this evaluation (PSG), such as those colonized by Pseudomonas aeruginosa and those with persistent reduction in pulmonary function (especially FEV1), if not the general population of CF patients.